Submanifolds of Sasakian Manifolds with Certain Parallel Operators. (2nd February 2014) - Ishan, Amira A.
Abstract : We study submanifolds of Sasakian manifolds and obtain a condition under which certain naturally defined symmetric tensor field on the submanifold is to be parallel and use this result to obtain conditions under which a submanifold of the Sasakian manifold is an invariant submanifold.